The Implementation of Interactive Reading Model to Teach Reading - Irmawati; Kisman Salija; Geminastiti Sakkir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This research aimed to explore (1) the implementation of the interactive reading model in teaching reading, (2) the supports and hindrances in implementing the interactive reading model, and (3) the students’ perceptions of this implementation. A qualitative method was employed, with participants selected through purposive sampling. The study involved one English teacher from the academic year 2023/2024 and nineteen students from SMAN 2 Sinjai, categorized by reading proficiency: six proficient readers, seven with moderate skills, and six struggling readers. Data were gathered via classroom observations, teacher interviews, and student questionnaires. Findings indicated that during pre-reading, the teacher introduced the text topic, explained text structure, and encouraged active student participation. During while-reading, emphasis was placed on pronunciation, intonation, understanding, and grammatical explanations, with students encouraged to predict and transfer information. Post-reading activities involved varied tasks. Supports included available technology (projectors and printers) and teacher experience, while challenges involved preparing engaging materials and managing afternoon classes. Hinders were large class sizes and low student participation, addressed through small group discussions, positive motivation, and suitable materials. The interactive reading model significantly boosted student enthusiasm, critical thinking, and active participation, with students showing high interest and positive attitudes towards the learning material. Overall, the implementation of the interactive reading model was found to be effective in enhancing students’ motivation, reading skills, and classroom engagement. In conclusion, the interactive reading model is a viable approach to teaching reading, demonstrating considerable benefits in terms of student engagement and skill development. However, it requires substantial preparation and adaptation to specific classroom contexts. Recommendations include further training for teachers in interactive reading techniques, the integration of more diverse and engaging materials, and continued research into the long-term impacts of interactive reading models on student learning outcomes.